2015
DOI: 10.11648/j.jfns.s.2015030102.21
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different sanitizers in inactivating E. coli O157:H7 in Tomato and Cucumber

Abstract: Fresh produce is popular worldwide because it is recognized as an important source of nutrients, vitamins and fiber for humans. However, in the last two decades outbreaks of food borne illness and cases associated with fresh produce have increased significantly. This study was conducted to evaluate the efficacy of acidic electrolyzed water (EO) and alkaline water (AlcO), 200-ppm chlorine water, 3% H 2 O 2 and/or sterile distilled water wash in reducing Escherichia coli O157:H7 on the surface of dip-inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Again, foodborne illness due to contaminated vegetables increased many folds worldwide and many research studies reported that the presence of pathogenic bacteria like E. coli O157:H7, Salmonella spp., Listeria spp., Staphylococcus spp., Yersinia enterocolitica etc. in various fresh vegetable samples of Dhaka city markets (Islam et al., 2015; Jeddi et al., 2014; Kabir et al., 2014). In addition, when these pathogens were found resistant to multiple antibiotics, could pose significant public health risk and resistance of pathogenic bacteria could leads to the anti-infective therapy of both humans and animals (Lai et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Again, foodborne illness due to contaminated vegetables increased many folds worldwide and many research studies reported that the presence of pathogenic bacteria like E. coli O157:H7, Salmonella spp., Listeria spp., Staphylococcus spp., Yersinia enterocolitica etc. in various fresh vegetable samples of Dhaka city markets (Islam et al., 2015; Jeddi et al., 2014; Kabir et al., 2014). In addition, when these pathogens were found resistant to multiple antibiotics, could pose significant public health risk and resistance of pathogenic bacteria could leads to the anti-infective therapy of both humans and animals (Lai et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 119 samples, E. coli was isolated from 55 samples, with a prevalence of 46% for this investigation. Isolation of E. coli from raw vegetables is also published in Dhaka city by several researchers (Islam et al, 2015;Kabir et al, 2014). But the prevalence ratio is relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…Lettuce, tomato [12,13] Shigella spp. Lettuce, salad vegetables [14] Yersinia enterocolitica Carrots, cucumber, lettuce, and tomatoes [15][16][17] Viruses Hepatitis A and Norovirus Lettuce [18,19] Protozoa Cryptosporidium spp. and Cyclospora spp.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%